Penentuan Harga Pokok Produksi Menggunakan Metode Full Costing untuk Penetapan Harga Jual Pada Saskia Knitting - Fitriawati Fitriawati; Sugih Sutrisno Putra; Iyeh Supriatna; Rendra Trisyanto Surya; Khozin Arief (Indonesian Accounting Literacy Journal, 2026)
This research was conducted to compare the calculation of the cost of goods manufactured by Saskia Knitting as a knitwear manufacturer and calculations using the full costing method. The research method used by the author is descriptive research and data collection techniques are carried out by interviews and documentation. This study used 5 knitwear products, namely vests, chest zippers, full zippers, zakat, and T-shirts. The results of this study found that the cost of production with the full costing method has a higher value than according to the company. This happens because the calculation of the cost of production according to the company contains factory overhead costs that are not included. In addition, the profit according to the calculation of the cost of production using the full costing method and the selling price from the company has a lower value, so a new selling price is calculated for 3 knitwear products, namely vests, chest zippers and full zippers. The range of differences for the cost of production and profit from calculations carried out by Saskia Knitting using the full costing method is 11.59%-16.54%.